Childproof your Mac. IN Features. - Marshall, Gary.; Mead-Green, Rob.
Kids all ages love using Macs -- and that means risking them seeing, doing, and deleting things they shouldn't. This comprehensive guide shows you how to keep your beloved hardware safe--oh, and your kids too!
Keywords: Mac OS; iTunes; Time Machine; Parental controls; iMovie